Pengenalan Obat dan Gaya Hidup untuk Penderita Ulkus Peptikum dan GERD - Fajar Amirulah; Magfirah Magfirah; Maria Caecilia Novi Yanti; Murida Rusanda; Maria Vivian Wea Zi; Ella Soriarti Nurdin; Indah Ananda Putri; Artha Permata Hati Malau; Meretsha Nurjanah; Wardah Amalia Amal; Enjlin Parhusip; Vrilly Laturake (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Peptic ulcer is a condition where there is a wound or ulcer on the inner lining of the stomach. Gastroesophageal Reflux Disease (GERD) occurs when stomach contents flow back into the esophagus and can damage the mucosal lining of the esophagus. Extension activities carried out at SMA Santo Lukas 1, obtained pre-test results for correct answers of 82.08% and for wrong answers of 17.92%, while the post-test results showed a significant increase after the provision of material, namely for correct answers of 93.33% and wrong answers of 6.67%. This shows that most students understand the information delivered through counseling activities regarding GERD and peptic ulcers.